2016
DOI: 10.1016/j.jpsychires.2016.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial dysfunction and lipid peroxidation in rat frontal cortex by chronic NMDA administration can be partially prevented by lithium treatment

Abstract: Chronic N-methyl-d-aspartate (NMDA) administration to rats may be a model to investigate excitotoxicity mediated by glutamatergic hyperactivity, and lithium has been reported to be neuroprotective. We hypothesized that glutamatergic hyperactivity in chronic NMDA injected rats would cause mitochondrial dysfunction and lipid peroxidation in the brain, and that chronic lithium treatment would ameliorate some of these NMDA-induced alterations. Rats treated with lithium for 6 weeks were injected i.p. 25 mg/kg NMDA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 62 publications
1
10
0
Order By: Relevance
“…As OLZ treatment of macrophages increased superoxide and ROS, which includes hydrogen peroxide, these results indirectly suggest that this drug may cause mitochondrial dysfunction. Attenuation of ROS production by Li exposure may be possible as described in an investigation performed by Kim et al [51]. This study demonstrated that mitochondrial dysfunction and lipid peroxidation in rat frontal cortex triggered by chronic NMDA administration was partially reversed by Li treatment.…”
Section: Discussionsupporting
confidence: 63%
“…As OLZ treatment of macrophages increased superoxide and ROS, which includes hydrogen peroxide, these results indirectly suggest that this drug may cause mitochondrial dysfunction. Attenuation of ROS production by Li exposure may be possible as described in an investigation performed by Kim et al [51]. This study demonstrated that mitochondrial dysfunction and lipid peroxidation in rat frontal cortex triggered by chronic NMDA administration was partially reversed by Li treatment.…”
Section: Discussionsupporting
confidence: 63%
“…These data provide a causal link between LPO and mitochondrial dysfunction in HD (Lee et al 2011a). In rats, chronic injection of N-methyl-D-aspartate (NMDA) causes a decreased activity of mitochondrial complex I and II, as well as increased levels of LPO markers in brain tissue (Kim et al 2016), indicating a role of LPO in excitotoxic neuronal cell death. Similarly, excitotoxicity and LPO seem to be involved in ALS-associated cell death (Kruman et al 1999; Pedersen et al 1998; Shibata et al 2001; Ferrante et al 1997).…”
Section: Phospholipids and Mitochondrial Dynamics In Neurodegenerationmentioning
confidence: 99%
“…Some investigators reported that oxidative inflammatory mechanisms have been hypothesized to perform a role in the onset of metabolic adverse effects related to olanzapine administration [24]. Olanzapine treatment of macrophages elevated superoxide and ROS, such as hydrogen peroxide, these findings suggest that olanzapine may lead to mitochondrial dysfunction [25].…”
Section: Discussionmentioning
confidence: 99%